RANCANG BANGUN SISTEM KEAMANAN KENDARAAN DILENGKAPI DENGAN TEKNOLOGI GPS DAN SMS GATEWAY - Abdi Chaerunnas; Mery Subito (Foristek, 2020)
Vehicle theft is one of the most common cases in big cities. The absence of a security system on a vehicle is one of the causes of the case. Therefore, we need a security system on the vehicle in the form of an alarm and can also perform the tracking function. This study aims to design a vehicle security system using GPS and SMS Gateway technology. This system uses the u-blox Neo6m GPS module, GSM SIM 800L v2 module and Arduino Uno microcontroller. The tracking system uses data from GPS coordinates sent to the user's smartphone number and displayed on the Google Maps application. The accuracy of GPS coordinates in this system when compared to GPS on smartphones has a gap of between 1 - 26 meters. The response time when the user sends a command to track the vehicle to get a reply sms that is ± 37.6 seconds.